Maintenance staff scheduling system using heuristic-greedy algorithm / Nurliyana Sabli - Sabli, Nurliyana (2010)
This maintenance staff scheduling system was developed in order to overcome the problem that involved with managing staff. In this case, the system focused on scheduling staff for maintenance purpose. The objective of this system is to develop a system that that can automatically assign the staff to a task and to test the functionality of the prototype. The scheduling part will be developed using heuristic – greedy algorithm. The schedule part will start by checking the availability of staff at that day. If the staff is available and still does not have any task assigned, the system will automatically assign the task to the staff. Other situation happen if the staff already occupied with other task, where certain condition will be applied to check the availability of the staff. This prototype will help IT Unit to assign their staff to maintenance staff with more efficient.